HUBUNGAN BUDAYA SEKOLAH DAN KETELADANAN GURU DENGAN KARAKTER SISWA SEKOLAH DASAR NEGERI 050772 KECAMATAN PANGKALAN SUSU KABUPATEN LANGKAT - Khairani Nasution (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This research aims to know how the relation of primary School 050772 Pangkalan Susu. The sample of this research 30 student where 21% taken of 141 students. This research uses data collection tool in the form of Likert scale. Questioner is compiled based on variabel and tested to respondent that is not research sample. Data analysis process is conducted by using quantitative approach through three steps, they are: 1. Describing research variabel data. 2. Testing requirements analysis. 3. Testing hypotesis to reveal the relation the relation beetween research variables using correlation analysis technique. Based on data analysis result and testing process, then the conclusion is (1) the school culture has positive relation with student’s character of primary school 050772 Pangkalan Susu. This case is proved that the correlation r (0,504) > r table (0,3061) while the significance is 0,004 < 0,05; (2) the teacher’s example has positive relation with student’s character of primary School 050772 Pangkalan Susu where correlation coeficient r (0,603) > r table (0,3061) with significncy 0,006, it is fewer than 0,05; (3) School Culture and teacher’s example has positive ration with student’s character of primary school 050772 Pangkalan Susu where correlation coefisiency r (0,662) > r table (0,3061), testing result F shows that F count (10,506) > F table (3,35) while significancy < 0,05 that is 0,000. Based on the research above, it can be stated that student’s character can be formed through school culture and teacher’s example.